The Effect of Tax Volunteer Programs and Tax Training on Students Interest in A Career in Taxation (Study on Accounting Students in Bandung) - Sephianingmas, Risna Wahyu; Rakhmadani, Vania (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2025)
Introduction/Main Objectives: This study aims to determine the influence of tax volunteer programs and tax training on the interest of accounting students in Bandung to pursue a career in the field of taxation. Background Problems: The phenomenon this study is the high interest of students in choosing accounting majors, which will affect the level of competition in the world of work. Novelty: This study has a gap in results between previous studies and the absence of similar studies conducted in the city of Bandung. Research Methods: This study uses a quantitative method with a descriptive and verification approach. The population in this study were accounting students in Bandung, with a sampling technique using purposive sampling. The number of samples used in this study was 100 respondents. The data sources used were primary data obtained through online questionnaires using Google Form and secondary data in the form of data on the number of accounting students in Bandung. The data analysis technique used in this study was multiple linear regression analysis. Findings/Results: The results of the study partially, the tax volunteer program influenced students' interest in pursuing a career in taxation. Likewise, tax training influenced this interest. Simultaneously, the tax volunteer program and tax training influenced students' interest in pursuing a career in taxation. Conclusion: Based on the results of the analysis, it can be concluded that the Tax Volunteer program and tax training, both partially and simultaneously, have an effect on students' interest in pursuing a career in taxation.